2022
DOI: 10.3390/ijms23179512
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Pancreatic Cancer Cells and Cancer-Associated Fibroblasts in the Tumor Microenvironment Mediated by Exosomal MicroRNAs

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most malignant digestive tumors, characterized by a low rate of early diagnosis, strong invasiveness, and early metastasis. The abundant stromal cells, dense extracellular matrix, and lack of blood supply in PDAC limit the penetration of chemotherapeutic drugs, resulting in poor efficacy of the current treatment regimens. Cancer-associated fibroblasts (CAFs) are the major stromal cells in the tumor microenvironment. Tumor cells can secrete exosomes to promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…One study of patients with pancreatic cancer has found these EVs carry specific miRNAs that could serve as biomarkers for early detection of the disease. 83 Another study has shown that AD-MSC-secreted EVs could transfer functional mitochondria to recipient cells, which could potentially be used to rescue damaged cells or tissues. 84 Raza et al investigated the influence of AD-MSC-derived EV-regulated ovarian cancer cells by studying A2780 and SKOV-3 cells and found that AD-MSC-derived EVs can inhibit A2780 and SKOV-3 cell growth and proliferation that could be related to cancer progression.…”
Section: Types Of Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study of patients with pancreatic cancer has found these EVs carry specific miRNAs that could serve as biomarkers for early detection of the disease. 83 Another study has shown that AD-MSC-secreted EVs could transfer functional mitochondria to recipient cells, which could potentially be used to rescue damaged cells or tissues. 84 Raza et al investigated the influence of AD-MSC-derived EV-regulated ovarian cancer cells by studying A2780 and SKOV-3 cells and found that AD-MSC-derived EVs can inhibit A2780 and SKOV-3 cell growth and proliferation that could be related to cancer progression.…”
Section: Types Of Stem Cellsmentioning
confidence: 99%
“…EVs derived from AD-MSCs have also been shown to play a role in intercellular communication with potential as biomarkers for disease diagnosis and prognosis. One study of patients with pancreatic cancer has found these EVs carry specific miRNAs that could serve as biomarkers for early detection of the disease . Another study has shown that AD-MSC-secreted EVs could transfer functional mitochondria to recipient cells, which could potentially be used to rescue damaged cells or tissues …”
Section: Types Of Stem Cellsmentioning
confidence: 99%
“…In addition, microRNAs (miRNAs) are recognized as small endogenous noncoding RNAs that have something to do with the progression of disease 9 . Exosomal miRNAs mediates crosstalk between PC cells and CAFs in TME 10 . Especially, miR‐21, an oncogenic factor, is involved in the regulation of pancreatic ductal carcinoma cell stemness 11 .…”
Section: Introductionmentioning
confidence: 99%
“…9 Exosomal miRNAs mediates crosstalk between PC cells and CAFs in TME. 10 Especially, miR-21, an oncogenic factor, is involved in the regulation of pancreatic ductal carcinoma cell stemness. 11 It has been documented that miR-21 expression and activated CAFs are increased in patients with GEM-resistant pancreatic ductal carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…The stroma is biologically highly active and significantly influences tumor growth, metastatic spread, and resistance to therapy [ 4 ]. Therefore, it is likely that CAFs influence the biology of PDAC through several mechanisms [ 5 , 6 , 7 ]. Primarily, CAFs influence malignant cells across a plethora of tumor types [ 8 ], including PDAC, by their paracrine production.…”
Section: Introductionmentioning
confidence: 99%